PENINGKATAN LITERASI BAHASA MELALUI MEDIA KARTU HURUF BERGAMBAR PADA SISWA KELAS I MI YAPPI PIJENAN GUNUNGKIDUL - Hariyatun; Umi Musaropah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Language literacy stands as a fundamental competence that plays a pivotal role for early-grade students, serving as a cornerstone for success in subsequent educational stages. This study seeks to optimize the reading literacy skills of first-grade students at MI YAPPI Pijenan by implementing illustrated letter cards within the instructional process. The methodology employed is Classroom Action Research (CAR), conducted through two cycles consisting of planning, action, observation, and reflection stages. A total of 12 first-grade students participated as research subjects. To ensure data accuracy, the researcher utilized various instruments, including direct observation, initial reading assessments, interviews, and documentation. The findings indicate a progressive improvement in the students' ability to identify letters, articulate letter sounds, and read both syllables and simple words. Furthermore, student motivation and engagement during learning activities showed a positive trend. Significant progress was recorded from the pre-intervention phase to Cycle II, with classical mastery exceeding the 75% threshold across all indicators. From a theoretical perspective, the effectiveness of these illustrated cards is supported by dual-coding theory and multimodal learning, which emphasize the integration of visual and verbal information during cognitive processing. In practice, this media has proven to be an effective, interactive, and applicable strategy for teaching reading to young learners. Ultimately, this study demonstrates that concrete visual media helps students bridge the gap between letters, sounds, and meanings, thereby strengthening their decoding skills while fostering self-confidence and active participation.